Populism and socio-political cleavages in Central Europe: The case of Slovakia - Anatoliy Klyuchkovych (Masyarakat, Kebudayaan dan Politik, 2026)
This article explores the relationship between populism and socio-political cleavages in the post-socialist democracies of Central Europe, using Slovakia as a case study. This study is based on the assumption that classical cleavages are no longer sufficient to explain contemporary party competition; therefore, the focus is placed on new situational lines of division that create opportunities for various forms of populism. This study aims to analyze the impact of situational socio-political cleavages on the variation in populist forms in Slovakia and identify the political actors that most clearly represent these divisions. Methodologically, the research combines an analytical case study with a discursive analysis of program documents and political rhetoric, supported by empirical datasets to assess the intensity and typology of populism. The findings demonstrate that situational cleavages catalyze populist mobilization driven by short-term crisis triggers. In this context, personalist, anti-corruption, anti-immigration, and sovereigntist–Eurosceptic divisions are identified, each activating a corresponding type of populism. The study shows that the Slovak case represents a Central European configuration of situational cleavages that shape the types, dynamics, and institutional consequences of populism in the country. This study concluded that such divisions function as key mechanisms of populist political mobilization.